Pengaruh Faktor-Faktor Kemasan Produk terhadap Keputusan Pembelian Konsumen Pop Mie di Supermarket Giant Wiyung - Yessy Artanti; Yusdia Pusparini (Universitas Negeri Surabaya, 2018)
This study aimed to investigate the influence factors of product packaging to Pop Mie consumer purchase decision at Wiyung Giant Supermarket. Product packaging factors in this case includes visibility, information, emotional appeal, and power/ ability to do (workability). The population used in this study is to visitors of the Wiyung Giant Supermarket who was buying Pop Mie. Technique to determine the members of the sample in this study is using accidental sampling technique. The number of samples is 105 respondents. This research notes that the results of hypothesis testing through F test states that the visibility, information, emotional appeal, and power/ ability to do (workability) have significant influence simultaneously to the consumer purchases decision(Y). This conclusion is based on the results of the analysis that shows calculated F value of 28.199 with an error rate prediction / forecast of 0.000 with a value smaller than 0.05 or 5%. Based on t test, it can be known that all the free variables which consist of visibility, information, emotional appeal, and power/ ability to do (workability) partially have a significant influence on the dependent variable, the consumer purchase decision. This was proved by the level of significance for each independent variable is smaller than at 0.05 or 5%. The result of T test shows that information variable has regression coefficient = 0.742 and calculated t = 9.202 with a significance level of 0.000. So that, information variable has the most influence to consumer purchase decisions of Pop Mie at Wiyung Giant Supermarket.